Shadow players: Western consultancies in the Arab world. How multinational consulting firms shape public policy - Dawud Ansari; Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2023)
Across public sectors in the Arab world, international consultancy firms already play a pivotal role and are further expanding their operations. Among other projects, consultancies have (co-)designed such high-profile strategies as Saudi Arabia's "Vision 2030" and Morocco's "Green Agenda". Currently, they are stepping up their activities in national energy and climate strategies. Their operations involve almost no local public participation, which diminishes the legitimacy and quality of the policies crafted and undermines local development. Besides the ramifications for the Arab world, the consultancies' work in that region also affects German and European interests, even when it is commissioned by European actors or international organizations. If negative impacts are to be avoided, greater awareness and more transparency about the consultancies' activities are needed. Moreover, it is crucial to scrutinise whether, when and to what extent it is expedient to commission international consultancy firms.
Keywords: 320; international consultancy firms; “ ‎ Vision 2030” (Saudi Arabia); “ ‎ Green Agenda” (Morocco‎ ); Morocco; Jordan; Egypt; Gulf states; McKinsey